Thai Dance for Aesthetic Enhancement through the Light and Sound Performance, çKhon Dee Sri Ayuthaya - Chancharund, Rattasard; Charassri, Naraphong (Fine Arts Journal: Srinakharinwirot University, 2015)
The purposes of this dissertation were to study the patterns and the creativity of the traditional Thai dance for aesthetic enhancement by observing the light and sound performance of Khon Dee Sri Ayutthayaand to create and conserve the traditional Thai dance in order to pass on to the next generation. The performance of this traditional Thai dance was created by Assistant Professor Dr. Lady Winita Diteeyon, the national artist, and was directed by Professor Dr. Narapong Charassri. The first display of this Thaidance was on 27th December 1992 at Chai Wattanaram Temple in Ayutthaya on the occasion of celebrating His Majesty the Queen Sirikit’s the fifth cycle birthday. The research instruments were consisted of 6 types: 1) Research literature review 2) Specialist interview 3) Seminar 4) Multi media 5) Field study 6) Criteria of traditional Thai Dance. The period ofcollecting data started from December 2011 to July 2013. The data of the research was analyzed accordingto the traditional Thai Dance performance criteria. The result of the research found that there were 6features: 1) Role play 2) Dance patterns 3) Costume design 4) Sound & Music design 5) Light display 6) Performer. In addition, the result of the research in creativity of Traditional Thai dance for aestheticenhancement found that there were many findings: 1) Variety of cultural dance patterns 2) Symbolic inthe dance 3) Performing arts and visual arts based on the theories 4) Various dance patterns 5) Reflecting the ways of Thai living and society 6) Focusing on creativity 7) Conserving the ways of Thai life 8) Concerning morality 9) Creating and enhancing the aesthetic arts 10) Communicative performance and conveying the meaning of the display 11) Concerning the perception of the young generation. The publication of this thesis has been supported by CU Graduate School Thesis Grants, the Graduate Schoolat Chulalongkorn University.